Association between a low‐carbohydrate diet and sleep status, depression, anxiety, and stress score. (24th February 2020) - Daneshzad, Elnaz; Keshavarz, Seyed‐Ali; Qorbani, Mostafa; Larijani, Bagher; Azadbakht, Leila
Abstract: BACKGROUND: Dietary intakes, especially carbohydrates, play an important role in blood glucose control in patients with diabetes. It is suggested that carbohydrate amounts may be effective in diabetes complications. This study aimed to reveal the association of low‐carbohydrate diet (LCD) and sleep and mental status among patients with diabetes. METHODS: This cross‐sectional study was conducted among 265 women with type 2 diabetes. Anthropometric measures, as well as biochemical tests, were recorded. Dietary intakes were recorded using a validated food‐frequency‐questionnaire to calculate LCD score. To assess mental disorders and sleep quality, the Depression, Anxiety and Stress Scale and the Pittsburgh Sleep Quality Index were used respectively. RESULTS: Patients in the highest LCD quartile were the ones with the lowest carbohydrate consumption. There was no significant association between cardiovascular risk factors and LCD score even after controlling confounder variables ( P > 0.05). Subjects in the highest quartile of LCD score compared with those within the lowest quartile had a 69% lower risk of poor sleep after adjusting confounders. The odds of depressive symptoms were negatively related to the highest quartile of LCD score in the crude model and even after full‐adjusted model (odds ratio: 0.42; 95% confidence interval: 0.17–1.01). Participants in the highest quartile of LCD score compared with those in the lowest quartile had a 73% lower risk of anxiety. CONCLUSION: It seems that patients who consumed lower carbohydrate have better sleep status and are less involved with mental disorders. However, regarding the nature of the present study, well‐designed cohort studies are suggested to be conducted in the future. © 2020 Society of Chemical Industry